Evaluation of Street Lighting Levels on Road User Safety and Security : Case Study Cikijing - Majalengka - Nanda Endi S; Mohamad Taufik; Ade Jaya Saputra (Fakultas Teknik Sipil dan Perencanaan, 2025)
Road infrastructure is an important foundation for economic growth and the movement of people around the world. Road lighting also plays a vital role in safe driving at night. Roads are local infrastructure that facilitate trade, tourism and cross-border interaction. Traffic acts as a means of land transportation that makes it easier for individuals to travel and companies to distribute their products to various regions. Therefore, creating a safe and comfortable environment for the community involves various aspects, one of which is lighting. In the context of driving safety, the case that occurs on the Cikijing - Majalengka road is the absence of adequate road lighting, endangering road users at night. Adequate lighting plays an important role in preventing crime, because criminals tend to avoid areas that are well lit and easily monitored. The location of this research was carried out on the Cikijing - Majalengka highway, more precisely on the Cikebo Block highway, Maja District. This research uses qualitative methods to analyze perceptions. because this method is more suitable for answering research questions that cannot be answered quantitatively. This study measured respondents' perceptions of street lighting based on two parameters: level of importance and level of satisfaction. Measurements were made using a Likert scale of 1 to 5 with a range from “not important” to “very important” for importance, and from “not satisfied” to “very satisfied” for satisfaction. The data collected was then analyzed using the (IPA) method. Based on data collected from 50 respondents, the Cikijing-Majalengka road user profile is dominated by men, with the majority aged ≤ 20 years, and the most commonly used vehicle is a motorcycle. Users over 60 years of age are relatively rare on this road section.